2018
DOI: 10.2478/acph-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC determination of diosgenin in fenugreek seeds

Abstract: A new HPTLC-densitometric method for diosgenin determination in fenugreek seeds was established after optimization of the conditions for efficient saponin extraction and acid hydrolysis. Several procedures were tested, the best of which was a three-step Soxhlet extraction, followed by hydrolysis of the obtained methanolic extract with 2 mol L-1 H2SO4. Best diosgenin separation from other hydrolysis products was obtained on HPTLC Si60F254 plates u sing a mixture of n-heptane/ethyl acetate (7:3, V/V) and modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 15 The best-known source of various steroidal saponins, including spirostane and furostane types, is fenugreek ( Trigonella foenum graecum ) seeds. 16 In recent years, diosgenin has attracted increasing attention due to its efficacy in treating various metabolic diseases, including diabetes, 17 CVDs, 18 neurological disease, 19 osteoporosis, 20 and hyperlipidemia, 21 in addition to anti-cancer effects, which are mediated via multiple targets and regulate various signals. 22 , 23 Numerous animal experiments and clinical trials have shown that diosgenin can reduce blood lipids by lowering plasma low-density lipoprotein (LDL) and increasing high-density lipoprotein (HDL).…”
Section: Introductionmentioning
confidence: 99%
“… 15 The best-known source of various steroidal saponins, including spirostane and furostane types, is fenugreek ( Trigonella foenum graecum ) seeds. 16 In recent years, diosgenin has attracted increasing attention due to its efficacy in treating various metabolic diseases, including diabetes, 17 CVDs, 18 neurological disease, 19 osteoporosis, 20 and hyperlipidemia, 21 in addition to anti-cancer effects, which are mediated via multiple targets and regulate various signals. 22 , 23 Numerous animal experiments and clinical trials have shown that diosgenin can reduce blood lipids by lowering plasma low-density lipoprotein (LDL) and increasing high-density lipoprotein (HDL).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that three‐step Soxhlet extraction with petroleum ether, chloroform, and methanol followed by acid hydrolysis displayed better extraction efficiency of volatile components from both the bittered and debittered fenugreek seeds samples compared to direct extraction with methanol under reflux and ultrasound extraction. Scanning was performed after derivatisation using modified anisaldehyde reagent at 426 and 590 nm 65 . According to the current review, it could be concluded that HPLC and HPTLC are the most common techniques used for quality control of fenugreek products compared to other methods which are described later.…”
Section: Chromatographic Techniquesmentioning
confidence: 99%
“…This technique has been applied by the World Health Organization (WHO), the State Food and Drug Administration of China (SFDA) as a strategic plan for the quality assessment of TCM [9,10], and got increasing concerns because it focuses on the characterization of the total sample composition. Several ways, for instance, high-performance thin layer chromatography (HPTLC) [11][12][13][14], thin-layer chromatography (TLC) [15][16][17], infrared spectroscopy (IR) [18][19][20], mass spectrometry (MS) [21,22], gas chromatography (GC) [23,24], high-performance liquid chromatography (HPLC) [25][26][27], nuclear magnetic resonance (NMR) [28][29][30][31] and high-performance liquid chromatography (UPLC) [32][33][34] are utilized for fingerprinting to characterize multiple compounds in the tested herbal samples. Among the abovementioned methods, HPLC is generally the most applied method for its high sensitivity, selectivity, and low cost [35].…”
Section: Introductionmentioning
confidence: 99%